Female reproductive success in a species with an age‐inversed hierarchy. Issue 6 (November 2016) - DE VRIES, Dorien; KOENIG, Andreas; BORRIES, Carola
Abstract: In most group‐living mammals, reproductive success declines with increasing age and increases with increasing rank. Such effects have mainly been studied in matrilineal and in "age positive" hierarchies, which are stable and in which high ranking females often outperform low ranking ones. These relationships are less well‐understood in age‐inversed dominance hierarchies, in which a female's rank changes over time. We analyzed demographic data of 2 wild, unprovisioned groups of gray langurs ( Semnopithecus schistaceus ) near Ramnagar, Nepal covering periods of 5 years each. Female rank was unstable and age‐inversed. We measured reproductive success via birth rates (57 births), infant survival (proportion of infants surviving to 2 years) and number of offspring surviving to 2 years of age (successful births) for 3 age and 3 rank classes. We found that old females performed significantly worse than expected (birth rate P = 0.04; successful births P = 0.03). The same was true for low ranking females ( P = 0.04, and P < 0.01, respectively). Infant survival was highest for young and middle‐aged as well as for high and middle ranking females. Overall, the results for these unstable hierarchies were rather similar to those for stable hierarchies of other mammals, particularly several nonhuman primates. Compared to a provisioned population of a closely related species, the wild and unprovisioned population examined (i) showed stronger age effects, while (ii) female reproductive success was equally affected by rank. Future comparative studies are needed to examine whether captive or provisioned populations deviate predictably from wild populations.